Infectious mononucleosis with follicular tonsillitis and urinary tract infection - Mathur, Alok; Joad, Mohammad Izhar; Ravte, Veda Shree; Brar, Ajit Singh; Jain, Priyansha; Gupta, Jugal Bihari (Indian Journal of Case Reports, 2024)
Despite the prevalence of Epstein-Barr virus (EBV) infection, new reports of weird and atypical manifestations of the infection continue to emerge, raising the question of how well we know this pathogen. The clinical appearance of patients who become infected throughout their youth or early adulthood is changing as the infection age rises in developed countries. Other physical symptoms are less noticeable and liver involvement is more noticeable throughout these stages. To inform health-care professionals of this change, an update on infectious mononucleosis variable manifestation is necessary. This case presented a 28-year-old female presented with a history of fever, nausea, and vomiting with odynophagia and cervical lymphadenopathy. Complete blood count and peripheral blood film examination revealed lymphocytic leukocytosis with many reactive lymphocytes. Her monospot test for EBV was positive along with a urine culture positive for Staphylococcus aureus.